Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/geosciences8120479
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Drone Surveying of the Pista Geoglyph in Palpa, Peru

Abstract: Currently, satellite images can be used to document historical or archaeological sites in areas that are distant, dangerous, or expensive to visit, and they can be used instead of basic fieldwork in several cases. Nowadays, they have final resolution on 35–50 cm, which can be limited for searching of fine structures. Results using the analysis of very high resolution (VHR) satellite data and super resolution data from drone on an object nearby Palpa, Peru are discussed in this article. This study is a part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The use of sUAVs in disaster reconnaissance prevents researchers and surveyors from having to enter many high-risk areas and reduces the time spent collecting surveyed data at every desired point. A recent example of high resolution sUAV data acquisition is Pavelka et al [16] of the Pista Geoglyph in Peru, and expertise with sUAVs (and LiDAR) as shown in Pellicani et al [17] demonstrates that sUAVs support and compliment geomorphic interpretations of disaster sites. Creating useful and accurate models with SfM software requires a series of photos at various normal and oblique angles that eventually tie into ground control points (GCPs) in a 3D reconstructed model.…”
Section: Methods Of Preliminary Suav Reconnaissance and Modeling In 2016mentioning
confidence: 99%
“…The use of sUAVs in disaster reconnaissance prevents researchers and surveyors from having to enter many high-risk areas and reduces the time spent collecting surveyed data at every desired point. A recent example of high resolution sUAV data acquisition is Pavelka et al [16] of the Pista Geoglyph in Peru, and expertise with sUAVs (and LiDAR) as shown in Pellicani et al [17] demonstrates that sUAVs support and compliment geomorphic interpretations of disaster sites. Creating useful and accurate models with SfM software requires a series of photos at various normal and oblique angles that eventually tie into ground control points (GCPs) in a 3D reconstructed model.…”
Section: Methods Of Preliminary Suav Reconnaissance and Modeling In 2016mentioning
confidence: 99%
“…The advantage of SfM is the simultaneous image matching, bundle adjustment, and reconstruction of a 3D structure on images. The principle itself, the sequence of individual processing steps, and the corresponding algorithms are generally well-known and frequently used (Seitz et al, 2006;Westoby et al, 2012;Remondino et al, 2014;Pavelka et al, 2018;Štroner et al, 2020;and others).…”
Section: Digital Close-range Photogrammetrymentioning
confidence: 99%
“…In the current practice of archaeological remote sensing where small Unmanned Aerial Vehicles (UAV)/Remotely Piloted Aircraft System (RPAS) are increasingly used by archaeologists as data acquisition platforms and (semi-)autonomous measurement instrumentation, the paper published by Pavelka et al [28] demonstrates the agility of this RS solution in arid environments and the opportunity that it can offer for fascinating discoveries while documenting cultural landscapes. The authors exploited very high resolution (VHR) satellite data and super resolution data from the drone to improve the digital documentation of the "Pista" geoglyph in Palpa, Peru, and refine the knowledge and interpretation of this geoglyph that had been researched several times by the archaeologists, but still poses some open questions.…”
Section: High Resolution Documentation Of Archaeological Features Witmentioning
confidence: 99%